3D-crumpled graphitic carbon nitride achieving promoted visible-light-driven molecular oxygen activation for phenol degradation. (April 2023) - Zhang, Hui; Wang, Chengwen; Li, Lei; Zhang, Jiaxin; Zhao, Jinbo; Sun, Tao; Cui, Baoshan
Abstract: Boosting optical absorption and charge transfer of g-C3 N4 is of great importance but a challenging task for developing metal-free high-performance photocatalyst. Herein, 3D-crumpled g-C3 N4 (DCN) is synthesized through a direct top-down thermal etching strategy. The thermal exfoliation of layered bulk g-C3 N4 (BCN) in air atmosphere induces partial distortion of heptazine-based g-C3 N4 nanosheet, which further self-assemble into 3D-crumpled network structure. Spectroscopic and photoelectrochemical characterization demonstrate that the unique DCN can not only remarkably extend the visible-light response region to 600 nm by awakening the n-π* electron transition, but also significantly promote O2 activation for selective H2 O2 generation owing to the intensified electron delocalization and charge transport ability. Thus, DCN catalyst realizes an excellent photocatalytic phenol degradation rate under visible light irradiation (0.690 h −1 ), far (4.4-fold) out from the BCN counterparts. This work enables synergistic optimization of optical absorption, charge transport and surface-active sites by constructing a 3D-crumpled structure, which expands the engineering toolbox of metal-free skeleton photocatalyst for developing practical and economical catalysts for environmental remediation. Graphical abstract: Image 1 Highlights: 3D-crumpled g-C3 N4 is fabricated by a top-down thermal etching strategy. The distortion of g-C3 N4 nanosheet actives the n-π* electron transition. 3D-crumpled structure promotes the excition dissociation and advance O2 activation. 3D-crumpled g-C3 N4 exhibits a significantly enhanced photocatalytic activity.